Exploring the Relationship Between Immunization and Stunting: Understanding the Impact of Vaccinations on Child Growth and Development - Mulyani, Itza; khairunnas, khairunnas; Ayunda, Hanif Muchdatul; Syafiq, Ahmad; Ahmad, Aripin; Muliadi, Teuku (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2023)
The study aimed to investigate the relationship between stunting and completeness of immunization among children under five years old in Indonesia. The study used a cross-sectional design with a quantitative approach, utilizing secondary data from the Indonesian Family Life Study (IFLS) V big data in 2014. The sample consisted of children aged 12-59 months from 13 provinces in Indonesia, representing 83% of the total population. Data were analyzed using SPSS and STATA programs. Statistical analysis was performed to determine the association between immunization status and stunting. The results showed a significant statistical relationship (p-value <0.05) between immunization status and stunting occurrence among children aged 12-59 months in Indonesia, with a p-value of 0.001 and a PR value of 1.2 (95% CI: 1.14-1.6). Children who receive incomplete immunization have a 1.2 times greater risk of stunting compared to those who receive complete immunization. The study concluded that completeness of immunization is associated with stunting among children under five years old in Indonesia. Therefore, it is essential to ensure complete immunization coverage to prevent stunting in this population.